Effect of Health Behavior Promotion Program on the Severity of Knee Osteoarthritis in Overweight Older Adults in the Community - Chaiwongsa, Jaruporn; Thurapra , Apinya; Namphaisan , Kingkarn; ไชยวงศา เกศกัญญา (Medical Journal of Sakon Nakhon Hospital, 2024)
Knee osteoarthritis is a common health problem in older adults. Typical symptoms include pain, swelling, stiffness, or joint deformity. This restricts mobility and destroys their ability to do daily activities. This quasi-experimental research study aimed to study the effects of a health behavior promotion program using quadriceps femoris muscle exercise combined with weight control and hot compresses on the severity of knee osteoarthritis for 34 overweight older adults in the community by simple random sampling. The research period was eight weeks. The research instruments were the experimental instrument, the health behavior promotion program and the data collection instruments consisted of 1) a demographic data questionnaire and health data record form 2) an Oxford knee score, and 3) an Osteoarthritis controlling behavior questionnaire. The data were analyzed using the descriptive statistics, repeated measure ANOVA, and paired sample t-tests. The statistical level of 0.05 was considered significance. The results of the study found that the severity of knee osteoarthritis after the 8th week of the experiment was significantly higher than before the experiment (F (1.47, 48.44) = 4.43, p = 0.03). Higher scores indicated lower severity of knee osteoarthritis. The mean body mass index (BMI) and waist circumference (WC) were significantly decreased (p < 0.05). The mean score of osteoarthritis controlling behavior after the 8th week of experiment was significantly higher than before experiment (p < 0.05).